2015
DOI: 10.1016/j.ceb.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

ROS-dependent signal transduction

Abstract: Reactive oxygen species (ROS) are no longer viewed as just a toxic by-product of mitochondrial respiration, but are now appreciated for their role in regulating a myriad of cellular signaling pathways. H2O2, a type of ROS, is a signaling molecule that confers target specificity through thiol oxidation. Although redox-dependent signaling has been implicated in numerous cellular processes, the mechanism by which the ROS signal is transmitted to its target protein in the face of highly reactive and abundant antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
504
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 723 publications
(543 citation statements)
references
References 34 publications
8
504
0
6
Order By: Relevance
“…It is important to mention once more that ROS are no longer viewed as just toxic by-products of mitochondrial respiration, but are now appreciated for their role in regulating various cellular signaling pathways [24]. Indeed, the adaptation to stressful conditions of our life is mediated via vitagene network in the body.…”
Section: Binding Metal Ions (Metal-binding Proteins) and Metal Chelatmentioning
confidence: 99%
“…It is important to mention once more that ROS are no longer viewed as just toxic by-products of mitochondrial respiration, but are now appreciated for their role in regulating various cellular signaling pathways [24]. Indeed, the adaptation to stressful conditions of our life is mediated via vitagene network in the body.…”
Section: Binding Metal Ions (Metal-binding Proteins) and Metal Chelatmentioning
confidence: 99%
“…The first includes an intermediate step involving the oxidation of Trx or GSH to the redox relay mechanism, and the second one likely results from the dissociation and subsequent activation of a target protein after H 2 O 2 oxidation of a scavenger enzyme (272). In addition, NO and its derivatives (S-nitrosothiols [SNO] and GSNO) are involved in signal transduction (103, 152, 276, 338).…”
Section: B From Signal Transduction To Posttranslational Modificationsmentioning
confidence: 99%
“…It has since become apparent that ROS also serve as signal molecules to regulate various biological processes, such as cell proliferation, differentiation, inflammation and regeneration (Finkel, 2011;Reczek and Chandel, 2015;Schieber and Chandel, 2014). The classic oxidative stress theory has been a broadly accepted explanation for aging and is the theoretical backbone for using antioxidants, such as vitamins and N-acetyl cysteine (NAC), as anti-aging supplements.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggested that ROS from mitochondria, known as mtROS, extend lifespan (Kawagishi and Finkel, 2014;Lee et al, 2010;Reczek and Chandel, 2015;Ristow, 2014;Wang and Hekimi, 2015;Yang and Hekimi, 2010a;Yun and Finkel, 2014). Various stimuli, such as mitochondrial dysfunction, calorie restriction, acute impairment of insulin signaling, glucose restriction or absence of a germline, can release mtROS to extend lifespan (Lee et al, 2010;Schaar et al, 2015;Schulz et al, 2007;Wei and Kenyon, 2016;Xie and Roy, 2012;Yang and Hekimi, 2010a,b;Zarse et al, 2012).…”
Section: Introductionmentioning
confidence: 99%